2019
DOI: 10.3390/ijms20040857
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress and Unfolded Protein Response in Breast Cancer: The Balance between Apoptosis and Autophagy and Its Role in Drug Resistance

Abstract: The unfolded protein response (UPR) is a stress response activated by the accumulation of unfolded or misfolded proteins in the lumen of the endoplasmic reticulum (ER) and its uncontrolled activation is mechanistically responsible for several human pathologies, including metabolic, neurodegenerative, and inflammatory diseases, and cancer. Indeed, ER stress and the downstream UPR activation lead to changes in the levels and activities of key regulators of cell survival and autophagy and this is physiologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(96 citation statements)
references
References 124 publications
2
94
0
Order By: Relevance
“…Moreover, a disturbance in UPR pathway might render neurons vulnerable to neuropathic pain stimuli (Huang et al, 2015;Zhou et al, 2017;Kang et al, 2018). The link between autophagy and ER stress via UPR has been investigated substantially (Deegan et al, 2013;Huang et al, 2013;Lupachyk et al, 2013;Sisinni et al, 2019;Yang et al, 2019). PERK pathway is essential for autophagy induction following ER stress (Lee et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a disturbance in UPR pathway might render neurons vulnerable to neuropathic pain stimuli (Huang et al, 2015;Zhou et al, 2017;Kang et al, 2018). The link between autophagy and ER stress via UPR has been investigated substantially (Deegan et al, 2013;Huang et al, 2013;Lupachyk et al, 2013;Sisinni et al, 2019;Yang et al, 2019). PERK pathway is essential for autophagy induction following ER stress (Lee et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular stress, free radical exposure, calcium depletion, and unfolded or misfolded protein accumulation in endoplasmic reticulum (ER) lumen lead to ER stress (Sisinni et al, 2019). Recent studies demonstrated that ER stress might be involved in the induction and maintenance of neuropathic pain (Ge et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy can prevent apoptosis induced by antitumor drugs and promote tumor drug resistance. However, autophagy cell death may be a death mode of apoptosis tolerant tumor cells, Autophagy has double effects on drug resistance of tumor cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…the accumulation of unfolded/misfolded proteins in the reticulum, may arise due to glucose deficiency, hypoxia, calcium imbalance and oxidative stress. ERS is associated with tumor development and metastasis in breast cancer since the high cell proliferation rate in tumors causes hypoxia, www.nature.com/scientificreports www.nature.com/scientificreports/ nutrients starvation and higher ROS production 52,53 . In particular, increased ROS production in cancer cells arises from oxidative phosphorylation, oxygen metabolism and NADPH oxidase functions leading to oxidative stress, described also in breast cancer 54 .…”
Section: Characterization Of Genes and Pathways Involved In Patients'mentioning
confidence: 99%